The role of social support and academic self-efficacy in enhancing academic engagement among undergraduates - Anierobi, Elizabeth Ifeoma; Amjad, Amjad Islam; Ubani, Favour Amarachi; Aslam, Sarfraz; Khasawneh, Mohamad Ahmad Saleem; Alshamsi, Huda (International Journal of Evaluation and Research in Education (IJERE), 2025)
Academic engagement is vital to students’ academic success, especially in higher education settings where motivation and support systems vary widely. This study investigated the influence of social support and academic self-efficacy on academic engagement among undergraduates of Nnamdi Azikiwe University. The main objectives were to determine the extent to which parental and peer support and students’ belief in their academic abilities correlate with their level of academic engagement. A correlational research design was used to guide the study. From a total population of about 20,000 undergraduate students enrolled in the 2023/2024 academic session, a sample of 403 students was randomly selected using a simple random sampling technique to ensure equal representation. Data were collected using three standardized instruments: the social support questionnaire (SSQ), the academic self-efficacy questionnaire (ASEQ), and the academic engagement questionnaire (AEQ). The data were analyzed using SPSS software. Pearson’s product-moment correlation and multiple regression analysis were used to test the research questions and hypotheses. Findings showed significant positive relationships between social support (both parental and peer), academic self-efficacy, and students’ academic engagement. These results highlight the importance of fostering supportive learning environments and building students’ confidence in their academic abilities. Practical implications suggest that universities should implement structured peer mentoring, parental involvement strategies, and workshops that enhance academic self-efficacy to improve student engagement and academic outcomes.